2019
DOI: 10.1111/1462-2920.14472
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of dominant attractants by key chemoreceptors mediates recruitment of plant growth‐promoting rhizobacteria

Abstract: Summary Chemotaxis to plant root exudates is supposed to be a prerequisite for efficient root colonization by rhizobacteria. This is a highly multifactorial process since root exudates are complex compound mixtures of which components are recognized by different chemoreceptors. Little information is available as to the key components in root exudates and their receptors that drive colonization related chemotaxis. We present here the first global assessment of this issue using the plant growth‐promoting rhizoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 61 publications
4
52
0
Order By: Relevance
“…Many studies have shown that chemotaxis towards root exudates is the first step of bacterial colonization of roots [49]. Organic acids, amino acids, sugars, quaternary ammonium salts, and secondary metabolites secreted by plants are all potential chemoattractants for beneficial bacteria [49][50][51][52]. Our results showed that strain EGB could also be attracted by root exudates.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Many studies have shown that chemotaxis towards root exudates is the first step of bacterial colonization of roots [49]. Organic acids, amino acids, sugars, quaternary ammonium salts, and secondary metabolites secreted by plants are all potential chemoattractants for beneficial bacteria [49][50][51][52]. Our results showed that strain EGB could also be attracted by root exudates.…”
Section: Discussionsupporting
confidence: 51%
“…We speculate that root exudates of cucumbers attracted the movement of strain EGB in the soil. Many studies have shown that chemotaxis towards root exudates is the first step of bacterial colonization of roots [49]. Organic acids, amino acids, sugars, quaternary ammonium salts, and secondary metabolites secreted by plants are all potential chemoattractants for beneficial bacteria [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial colonization of plant roots is a multi-stage process that involves recognition, movement towards attractants and attachment (15). Once attached, persistence and propagation on plant roots is dependent on metabolic fitness (52,53), resistance to plant protective mechanisms and inter-microbial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Plants and microorganisms secrete a broad range of chemical compounds which can impact bacterial growth and alter their physiology (Dennis et al, 2010;Yu et al, 2019). Plants are known to recruit certain bacteria while suppressing others through immune responses (Chowdhury et al, 2015;Feng et al, 2019). Differences in community structure are observed at different stages of root development, or depending on root anatomy (Humphris et al, 2005;Schmidt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%